2016
DOI: 10.1155/2016/8406172
|View full text |Cite
|
Sign up to set email alerts
|

New Catalytic Method for the Synthesis of 2,7-Dicycloalkyl-hexaazaperhydropyrenes

Abstract: An efficient method for the synthesis of 2,7-dicycloalkyl-2,3a,5a,7,8a,10a-hexaazaperhydropyrenes by the NiCl2·6H2O-catalyzed ring transformation reaction of 1,3,5-tricycloalkyl-1,3,5-triazines with 1,4,5,8-tetraazadecalin has been successfully developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…On the basis of our own and the published data, we proposed a probable mechanism (Scheme ) for the formation of pyrrolidino­[3′,4′:1,9]­fullerenes in the Ti­(O- i -Pr) 4 -promoted reaction of C 60 with 1,3,5-perhydrotriazines and EtMgBr. According to the proposed mechanistic scheme, the initial step of the reaction between C 60 and 1,3,5-perhydrotriazines gives the key intermediate, bis-diisopropoxytitanacyclopropane C 60 derivative A .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of our own and the published data, we proposed a probable mechanism (Scheme ) for the formation of pyrrolidino­[3′,4′:1,9]­fullerenes in the Ti­(O- i -Pr) 4 -promoted reaction of C 60 with 1,3,5-perhydrotriazines and EtMgBr. According to the proposed mechanistic scheme, the initial step of the reaction between C 60 and 1,3,5-perhydrotriazines gives the key intermediate, bis-diisopropoxytitanacyclopropane C 60 derivative A .…”
mentioning
confidence: 99%
“…As a continuation of this research and to develop a new, efficient method for the synthesis of unsubstituted pyrrolidino-[3′,4′:1,9]fullerenes, we studied the reaction of C 60 with 1,3,5perhydrotriazines generated in situ upon the reaction of alkylamines with paraformaldehyde in the presence of Ti(O-i-Pr) 4 −EtMgBr-promoting system. In view of the recently discovered 14 ability of 1,3,5-perhydrotrizines to undergo unusual ring opening upon treatment with Ni salts, we suggested that under the conditions we developed previously, namely, in the presence of Ti complexes, opening of the triazine ring can result in the formation of 2,5-unsubstituted pyrrolidino[3′,4′:1,9]fullerenes according to the following reaction scheme:…”
mentioning
confidence: 99%
“…In continuation of our research in the field of synthesis of annelated polyazapolicycles and aiming at development of an efficient method for producing previously undescribed hexahydrodioxadecaazadicyclopenta­[ e , l ]­pyrenes promising for practical use, we have studied a reaction for catalytic cycloaminomethylation of tetraazadifurazanodecalin. Such an approach to the design of annelated polyazapolycycles is based on our previously obtained positive results for a one-pot synthesis of hexaazaperhydropyrenes , or hexaazaperhydrodibenzotetracenes via cyclocondensation of tetraazadecalin or tetraazaperhydrotetracene with cycloaminomethylation reagents. 1,3,5-Trisubstituted 1,3,5-triazinanes have been recognized as efficient reagents for the reactions of aminomethylation and cycloaddition. During our preliminary experiments, it had been shown that noncatalytic interaction between 1,3,5-tricyclopropyl-1,3,5-triazinane and 1,4,5,8-tetraazadifurazano­[3,4- c ]­[3,4-h]­decalin ( 1 ) at 20 °C results in formation of 2,8-dicyclopropyl-substituted hexahydrodioxadecaazadicyclopenta­[ e , l ]­pyrene ( 2 ) with the yield no more than 10%.…”
mentioning
confidence: 99%
“…1,3,5-Trisubstituted 1,3,5-triazinanes have been recognized as efficient reagents for the reactions of aminomethylation and cycloaddition. During our preliminary experiments, it had been shown that noncatalytic interaction between 1,3,5-tricyclopropyl-1,3,5-triazinane and 1,4,5,8-tetraazadifurazano­[3,4- c ]­[3,4-h]­decalin ( 1 ) at 20 °C results in formation of 2,8-dicyclopropyl-substituted hexahydrodioxadecaazadicyclopenta­[ e , l ]­pyrene ( 2 ) with the yield no more than 10%. To increase the yield of the target heterocycle 2 , we have carried out the reaction of 1,3,5-tricyclopropyl-1,3,5-triazinane with 1,4,5,8-tetraazadifurazano­[3,4- c ]­[3,4- h ]­decalin in the presence of nickel catalyst that we had previously utilized in heterocyclization reactions. Under the action of NiCl 2 ·6H 2 O (5 mol %), heterocyclization between 1,4,5,8-tetraazadifurazano­[3,4- c ]­[3,4- h ]­decalin and 1,3,5-tricyclopropyl-1,3,5-triazinane proceeds in a MeOH–DMSO mixed solvent to produce hexahydrodioxadecaazadicyclopenta­[ e , l ]­pyrene 2 with 63% yield. Upon increasing concentration of the NiCl 2 ·6H 2 O catalyst up to 10 mol %, no significant changes in the yield of the heterocycle 2 has been observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation